Tensão, limites e possibilidades : assistentes sociais no cotidiano do Programa de Tratamento Fora do Domicílio na região de saúde de Alagoinhas/BA - Santos, Jeruzia Silva dos (2018)
The Professional Exercise of social workers in various socio-occupational spaces has been the object of multímodos studies, which enables an arsenal of research, productions and publications about the theme. In the area of health is undeniable and notorious the expressiveness of these studies, however, despite intense debates about the Interlocution Social Service with the sanitary reform and action of these professionals in health programs and projects, in relation to the professional exercise of social workers in the treatment program outside the home (PTFD) that is still incipient and shy. In this sense, the research on canvas permeates through research of the practice of professionals in the area of Social Services that operate in the PTFD having as general objective to analyze the demands and responses submitted by social workers in the everyday life of the said program ahead of the contradictions and tensions generated by the project focusing and private access to the universal right to health. Among other objectives, this study intends to characterize the profile of social workers inserted in the PTFD in municipalities of the region of health of Alagoinhas/BA; reflect on the socio-institutional determinants that impact the professional exercise of social workers; mapping the interventivas demands and actions of social workers in enabling access to health at PTFD and; check if the interventivas actions of social workers inserted in the PTFD are in line with the precepts of the laws that govern and regulate the professional exercise. In order to unravel some of the minutiae of daily life, we opted for the method of analysis historical materialism dialectic, configuring exploratory research with qualitative approach, using documentary sources of information, and oral literature, with the use of semi-structured interview techniques and systematic observation. The results obtained by the analysis of this research suggest, grosso modo, that social workers have exercised their work in the spaces of PTFD occupational health in the region of Alagoinhas, focus of the study, in concrete situations of work not conducive to compliance with the ethical conditions and techniques of professional exercise, given the precarious institutional conditions, the fragilities of employment contracts, low wages among other constraints of the dynamics of wage society in the current situation. As the demands of users these have been answered in the immediacy and emergency form presenting itself fragmented and heterogeneous, while the institutional demands have ordered new assignments, which are not always inherent in the prerogatives of professional social workers. Among the professional responses, we observed positions consistent with the laws that normatizam the profession. Also professional responses to identify possible trends reifying breeding practices of conservatism, conformatadas by intense bureaucratization in the light of pragmatism and praticismo, whose routine Social Worker finds no possibilities for critical reflection of the real in its entirety, Staying in a vision of everyday micro appearance of lived, succumbing, in many situations, a perception of the world which refracts the essence of the complexity of social life.